2013
DOI: 10.1177/0956462413490412
|View full text |Cite
|
Sign up to set email alerts
|

Associations between drug use and sexual risks among heterosexual men in the Philippines

Abstract: The relationship between drug use and sexual risk behaviours among 2272 men in the southern Philippines was assessed. Over 20% of participants used drugs. Logistic regression analyses adjusted for age, marital status, income, occupation and geographic region revealed that compared to non-drug users, men who used drugs had earlier sexual debuts (adjusted odds ratio = 1.73; 95% confidence interval = 1.38-2.17), were more likely to report two or more recent sexual partners (adjusted odds ratio = 2.22; 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Fifteen articles reported analyses from a longitudinal, quasi-experimental investigation of a community-based HIV prevention program involving female bar workers and managers in four regions of the Philippines [3953]. Four articles reported findings from a quasi-experimental intervention to prevent HIV and STIs among heterosexuals in southern Philippines [5457]. Two articles reported analyses of a survey of people who inject drugs in Manila, Cebu, and Davao cities [5859].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen articles reported analyses from a longitudinal, quasi-experimental investigation of a community-based HIV prevention program involving female bar workers and managers in four regions of the Philippines [3953]. Four articles reported findings from a quasi-experimental intervention to prevent HIV and STIs among heterosexuals in southern Philippines [5457]. Two articles reported analyses of a survey of people who inject drugs in Manila, Cebu, and Davao cities [5859].…”
Section: Resultsmentioning
confidence: 99%
“…Assessment of condom attitudes and knowledge also varied, with measurements including knowing that condoms prevent HIV/AIDS, pregnancy, and STI infections, as well as feeling that condoms reduce sexual pleasure or enjoyment, and that using condoms is against religion. Only five studies reported substance use outcome measures [21,34,38,57,62], and these studies varied with regard to assessment about type, frequency, and amount of substance use.…”
Section: Resultsmentioning
confidence: 99%
“…22 In a secondary analysis, male IDUs reported more frequent condom use when having sex with an FSW and with their regular partner. 23 The lack of condom negotiation among FSWs was associated with the use of an illegal substance. 24 …”
Section: Resultsmentioning
confidence: 99%
“…22 In a secondary analysis, male IDUs reported more frequent condom use when having sex with an FSW and with their regular partner. 23 The lack of condom negotiation among FSWs was associated with the use of an illegal substance. 24 In several studies, the reasons for not using condoms were did not think of using condoms, 19,25,26 discomfort and displeasure in condom use, 14,19,[26][27][28][29] interruption of sexual activity, 19,26,28 lack of available condom, 19,[25][26][27] and use of another contraceptive method.…”
Section: Intrapersonal Factorsmentioning
confidence: 99%